2012
DOI: 10.1063/1.3687186
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hall effect of reflected light from an air-glass interface around the Brewster’s angle

Abstract: We have developed a modified theory of the spin Hall effect of reflected light from a planar interface composed of two dielectric media and obtain the analytical expression valid for any incident angle including the Brewster’s angle. We improved the experimental method and measured the spin-dependent transverse displacement of reflected light from a planar air-glass interface around the Brewster’s angle. The experimental results are in agreement with the theoretical prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…On the other hand, supposing that the preselected state |H is incident near the Brewster angle, the operator exp(−ik y δ H ) cannot be expanded as 1 − ik y δ H due to the strong coupling [47][48][49][50]. Therefore, the weak value A w in Eq.…”
Section: Theoretical Modelmentioning
confidence: 92%
“…On the other hand, supposing that the preselected state |H is incident near the Brewster angle, the operator exp(−ik y δ H ) cannot be expanded as 1 − ik y δ H due to the strong coupling [47][48][49][50]. Therefore, the weak value A w in Eq.…”
Section: Theoretical Modelmentioning
confidence: 92%
“…Many efforts have been devoted to pursuing large spatial spin splitting 911 . It was found that, the OPSS can be enhanced when a Gaussian beam is reflected by an air-glass interface near the Brewster angle 12, 13 . Götte and coworkers found the eigenpolarizations of the OPSS 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Equation (9) will reduce to the expressions in previous works in special cases, for example, at partial reflection or neglecting the in-plane wave vector spread [11,14,28,31,32].…”
Section: Spin Separations In Shel For Reflectionmentioning
confidence: 97%
“…Although the L-LCP, R-LCP, L-RCP, and R-RCP have Gaussian profiles at an incident angle near θ B , the profiles of the total LCP (L-LCP+R-LCP) and RCP (L-RCP+R-RCP) components are severely distorted by the coherent superpositions, resulting in a large spin separation up to several microns. When the incident angle is far away from θ B , the SHEL shift is only a few tens of nanometers and the profiles are almost Gaussian [18,28,32].…”
Section: Spin Separations In Shel For Reflectionmentioning
confidence: 98%
See 1 more Smart Citation